Insights into spatial dynamics of the microbiome and resistome across the conventional and organic dairy farms - Kabilan Mani; Vignesh Palanisamy; Bhuwan Shrestha; Zachariah Vice; Sushil Paudyal; Sapna Chitlapilly Dass (PLoS ONE, 2026)
Antimicrobial resistance (AMR) poses a serious global threat to human and animal health. While AMR has been reported in various environments, its distribution across different ecological compartments within dairy farms remains poorly characterized. In this study, we used large-scale shotgun metagenomic sequencing to characterize the microbiome and resistome across multiple sampling sites within one organic and one conventional dairy farm, including teats, liners, water troughs, feed area, milking parlour mats, bedding sand, and milk. Our results indicate that microbial community composition and resistance gene profiles were largely comparable between the two study farms, with sample type (ecological niche) exerting a stronger influence on community structure than farm management type. Pseudomonadota, Bacillota, and Actinomycetota were the dominant phyla, while Aerococcus, Glutamicibacter, and Pseudomonas were the most prevalent genera. Glycopeptide resistance genes were the most abundant ARG class, followed by lincosamide and tetracycline resistance genes. Milk samples exhibited a distinct microbiome and resistome composition compared to environmental samples. Strong correlations between microbiome structure, resistome profiles, virulence factors, and metal resistance genes were observed across farm niches, highlighting the interconnected nature of microbial communities and resistance elements across dairy farm environments. These findings provide foundational data for targeted surveillance and management strategies to mitigate antimicrobial resistance in dairy production systems.